ANALISIS PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DESA (STUDI DI DESA WAWOLESEA KECAMATAN LASOLO KABUPATEN KONAWE UTARA) - Melis, Melis; Muthalib, Abd.Azis; Apoda, Apoda (JURNAL EKONOMI UHO, 2016)
This study aims to determine the level of public participation of development in Wawolesea Village  Lasolo District of North Konawe; and the factors that affect the level of public participation in the Wawolesea Village. The data obtained by questionnaires. Participation is measured by likert scale  from  respondent self assessment . Respondent of this study are 20 person consist: village administrative apparatus, communities, and institute for village empowerment (LPM). Data analyzed used descriptive. The results showed that the level of community participation of development in the Wawolesea Village  is in  very high category.  The community have  about  80.67 percent level participation in the planning or in very high category, 77.8 percent for imlementation or in high category, and  about  84.25 percent in utilization or in  very high category. While  for evaluation the community have about   79 percent or  in high category.  Determinant of public  participation in  Wawolesea Village   are awareness, education, income, village administrative apparatus and the facilities of village.